The Influence of Service Quality on Loyality with Satisfaction, Trust and Corpaorate Image as Intervening Variables in Rukun Tani Village Cooperative Unit in Pageruyung District Kendal Regency. - Maeriyana, Maeriyana; Soesilowati, Etty; Rozi, Fahrur (Universitas Negeri Semarang, 2019)
KUD (Village Cooperative Unit) becomes the main pillar of rural community’s economy which is a forum for the development of various rural community activities organized by and for the community itself. Therefore, support from various parties is needed to improve the progress of the KUD especially for its members to always be loyal to each of its business unit. The objective of the study is to analyze and identify the loyalty of members of the Rukun Tani Village Cooperative Unit who were influenced by the quality of service through satisfaction, trust and corporate image. The research method used is quantitative approach. The study population is 365 members and the sample is 191 members. The sampling technique used is proportional sampling. While the data analysis techniques used are descriptive analysis and path analysis. The results of path analysis showed that service quality has a direct effect on satisfaction, trust, corporate image, and loyalty. The service quality influences loyalty indirectly through satisfaction. The quality of service influences loyalty indirectly through trust. The quality of service influences loyalty indirectly through corporate image.